Implementasi Aqad Syirkah Sebagai Solusi Permodalan Untuk Kemajuan Bisnis UMKM - Loso, Loso; Tho’in, Muhammad; Romdhoni, Abdul Haris (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
Sharia economics is an economic discipline that focuses on Islamic sharia. Providing capital to business actors in the Sharia economy can be covered by a syirkah contract. The Syirkah contract is closely related to providing capital to MSMEs (Micro et al.). Through a syirkah contract, providing capital to MSMEs can be an effective tool. This research aims to determine the implementation of aqad syirkah as capital for the progress of MSME businesses. This research is descriptive qualitative research. The subjects of this research are business capital providers and MSMEs in Purwantoro District, Wonogiri Regency, as capital recipients. This research was conducted through interviews, observation and documentation, followed by qualitative data analysis. The research results showed that the approach to providing capital by implementing the Syirkah contract reflects the principles of sustainability and justice. In a syirkah contract, capital providers and MSME players share profits and risks by a predetermined agreement. The choice of type of syirkah contract, whether mudarabah or musyarakah, depends on the characteristics and goals of the business. Providing capital involves negotiation stages, establishing mutual requirements, dividing capital, and detailing profit sharing. In the context of a syirkah contract, the benefits for MSMEs include easy access to capital, higher motivation, and a significant contribution to business growth.